Is spinal manipulation therapy more effective than home exercise as a treatment for neck pain?. Issue 3 (March 2015) - Scott, Ryan; Satre, Thomas
Abstract : Evidence‐Based Answer : No, spinal manipulation is no more effective than home exercise for relief of acute or subacute neck pain (SOR: B, single RCT). For chronic neck pain in patients older than 65 years, the combination of spinal manipulation and home exercise may be more effective in the short term than home exercise alone, but this difference disappears in the long term (SOR: B, small RCTs). No studies used sham manipulation as a control.